Brand expertise and perceived consistency reversals on vertical line extensions: The moderating role of extension direction. (January 2017) - Pontes, Nicolas; Palmeira, Mauricio; Jevons, Colin
Abstract: Vertical line extensions are a valuable growth strategy for many retail service sectors. Correctly positioning a new vertical line extension in the price/quality spectrum is an important decision that has considerable implications for bottom line profits. This paper examines the moderating role of extension direction on the effect of perceived consistency on vertical extension evaluations. In two studies, we show that a lack of perceived consistency acts as a reminder to consumers that the brand may be stretching beyond its expertise, increasing perceived performance and financial risks for upscale extensions but not for downscale extensions. As a consequence, higher consistency results in higher upscale extension favourability whereas evaluations of downscale extensions are similar regardless of their perceived consistency with the parent brand.